"Остров достоверности": "детский" текст и его специфика - Сальникова, А. (Інститут історії України НАН України, 2008)
Salnikova. Island of Truth: Children’s Text and Its Specificity An article is devoted to the so-called children’s texts ─ the narrative documents produced by the children themselves. Special attention is given to the texts written by the Russian boys and girls during and after the 1917 Revolution. Though essentially different in their origins (Soviet/émigré, worker's/peasant's, classroom/independent etc.), types (school compositions, questionnaires, diaries, handwriting magazines and "annals", poems, fairy - tales etc.) and content, the majority of them represented a complicated mixture of specific children's culture of writi ng with a new – "revolutionary"– symbolic and semiotic code of that era. The article presents some of the examples of those texts’ semantic and semiotic analysis based on hermeneutic historic al source's reading.